Cristiano Ronaldo - Golkar, Golriz (2024)
"Engaging images accompany information about Cristiano Ronaldo. The combination of high-interest subject matter and light text is intended for students in grades 3 through 7"--
Goal!!! -- Who Is Cristiano Ronaldo? -- A rising star -- Soccer superstar -- CR7's future.
Includes bibliographical references and index.
Ages 7-12
Grades 4-6
Keywords: Ronaldo, Cristiano, -- 1985- -- Juvenile literature; Soccer players -- Portugal -- Biography -- Juvenile literature